Cognitive Development of 3-4 Year Old Children through Collage Activities at PAUD AN NADA Kedawung - S P, Lia Jumiati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
The purpose of this study was to determine whether there is a cognitive relationship between children aged 4-3 years through collage activities at An Nada Kedawung Elementary School. The benefit of this research is that it can be used as a comparison material for other researchers who examine the relationship between cognitive development of children aged 3-4 years with collage activities. This study uses a type of correlational research with a quantitative approach. Paud An Nada Kedawung was chosen as the research location based on the purposive area technique. The subjects in this study were determined using the population technique, so that the research subjects were all children aged 3-4 years in Paud An Nada Kedawung, Blitar Regency, totaling 16 people. The method of data collection was through observation and documentation, analyzed using the correlation level formula assisted by using SPSS calculator. The calculation result is 0.609 with a percentage of 37.09%. The results of this study indicate that there is a relationship between the cognitive development of children aged 3-4 years and collage activities at An Nada Kedawung Elementary School, Blitar Regency